1998
DOI: 10.1016/s0022-5347(01)62548-5
|View full text |Cite
|
Sign up to set email alerts
|

USE OF SECOND TREATMENT FOLLOWING DEFINITIVE LOCAL THERAPY FOR PROSTATE CANCER: DATA FROM THE caPSURE DATABASE

Abstract: Approximately 1 in 5 patients receive second cancer treatment within a mean of 3 years following initial local treatment for prostate cancer. Our data suggest that the likelihood of receiving second treatment was lowest in patients initially treated with radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 24 publications
1
42
2
2
Order By: Relevance
“…Tumour recurrence is common after primary therapy, occurring in 20-50% after RP during a 10 years follow-up [3,4], manifested by a rising PSA level, often without clinical or radiological evidence of disease. Moreover 16-35% of patients will receive second line treatments within 5 years from the initial therapy [5]. Freedland et al [6] showed that biochemical recurrence precedes clinical recurrence of a median of 5 years and that time to biochemical recurrence represents a predictive value for cancer specific survival.…”
Section: Introduction: the Clinical Pointmentioning
confidence: 99%
“…Tumour recurrence is common after primary therapy, occurring in 20-50% after RP during a 10 years follow-up [3,4], manifested by a rising PSA level, often without clinical or radiological evidence of disease. Moreover 16-35% of patients will receive second line treatments within 5 years from the initial therapy [5]. Freedland et al [6] showed that biochemical recurrence precedes clinical recurrence of a median of 5 years and that time to biochemical recurrence represents a predictive value for cancer specific survival.…”
Section: Introduction: the Clinical Pointmentioning
confidence: 99%
“…20 Up to a third of patients with biochemical relapse receive a second line treatment, usually without clinical or radiological evidence of disease. 19,21 The ability to distinguish local recurrence from systemic disease with posttreatment imaging may be critical because local recurrence is often amenable to local salvage treatment. 22 Some criteria, such as time to biochemical failure, PSA doubling time and positive surgical margins, were proposed to differentiate local recurrence from systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 However, a significant proportion of men (approximately 17 -35%) subsequently face disease progression following either surgery or radiotherapy and require further treatment. 12,13 This is either due to improper staging (tumors were not actually localized when treated) or much less often to inappropriate or suboptimal treatment. Moreover, significant morbidity is associated with the currently available therapeutic options.…”
Section: Management Of Localized Prostate Cancer: the Current Situationmentioning
confidence: 99%